ANALISIS DAN DESAIN PENERAPAN LOCATION BASED SERVICE (LBS) UNTUK LAYANAN PENGIRIMAN KATERING DI KOTA PALANGKA RAYA - Viktor Handrianus Pranatawijaya (Universitas Palangka Raya, 2018)
The quality of online catering services can be rated qualified or not with timely deliverysystem and provide quality assurance is maintained. Therefore, catering delivery services areconsidered important to be well managed. The catering delivery service applying LBS with theshortest route search using Dijkstra algorithm has several stages: (1) determining the location usedfor catering delivery service, (2) Determining the radius and point of customer's address location, (3)Create graphs and nodes based on existing road junctions and locations of catering customers; (4)Make scheduling of catering delivery services based on the shortest route of search using Dijkstraalgorithm (add the number of vehicles if the time does not meet and recalculate), (5) Conductingcatering delivery to customer's place based on the route formed and a notification will appearindicating that it has reached or approached the customer's address, and (6) Change the deliverystatus to be received. Application of Dijkstra algorithm can use Google Map and utilize Google MapAPI for its functions and on application of LBS recommended by using smartphone. The model usedis a model of modified Waterfall model. Stages performed only at the stage of analysis and design.